Development of Uno Biology Card Game Media on Reproductive System Material - Puspitasari, Milannia Eka; Sofiyana, Marinda Sari; Sholihah, Mar'atus (Journal of Natural Sciences, 2025)
The lack of interactive and engaging learning media often makes biology lessons, especially those involving sensitive topics such as the human reproductive system, feel monotonous and less effective for students. This research aims to develop a biology learning media in the form of a card game called Kartu Uno Biologi, adapted from the popular UNO game format. The goal is to improve student engagement, communication skills, and learning outcomes. The development model used in this study is ADDIE, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The media was validated by experts in material, media, and language, and was tested on students through small group trials and classroom implementation. The validation results showed that Krtu Uno Biologi was considered valid (68% from material experts) and very valid (86% from media experts). The practicality test showed that the media was easy to use with a score of 82.22%, and the effectiveness test indicated an improvement in students’ understanding and oral communication, with a normalized gain score of 0.669 (medium category). Based on these results, Kartu Uno Biologi is suitable for use as an alternative and effective biology learning tool.